SPIRITUALITY: A CONCEPT ANALYSIS - Mulyono, Wastu Adi; Purwandari, Haryatiningsih (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Introduction: Defining spirituality as a separate concept from its relationship to religious aspects has created discourses among experts. Consequently, spiritual needs are commonly unidentified by nurses during their nursing assessment activity. Moreover, they tend to refer this problem to another professional. Purposes: This study aims to clarify the concept of spirituality in the health context and to identify clear operational definition. Methods: Eight-step Walker & Avant’s concept analysis approach was implemented. The eight steps of the approach are as follows: 1) selecting concept, 2) determining the aim of the analysis, 3) identifying all uses of the concept, 4) determining the defining attributes of the concept, 5) constructing a model case, 6) constructing additional cases, 7) identifying the antecedents and consequences of the concept, and 8) defining empirical referents. Selecting concept and determining aim of the analysis put in introduction. Conclusion: Concept spirituality exist and different from religiosity; however, it will be beneficial to measure both religiosity and spirituality in the same situation.